Transmisi Memori Traumatis dalam Novel Ath-Thanturiyyah karya Radhwa ‘Asyur - Shinta Fitria Utami (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
The ath-Thanth?riyyah novel is a novel that tells the struggles of Palestinians who experienced the Nakba to become victims of the civil war that took place in Lebanon. Apart from narrating history, this novel portrays the traumatic memories of its characters. Therefore, the novel ath-Thanth?riyyah is a postmemory work. This article aims to analyze the process of transmitting traumatic memories experienced by the characters in the novel. This research utilizes the postmemory theory initiated by Marianne Hirsch. As for this research is a qualitative descriptive research. The results showed that there were two forms of traumatic memory transmission processes, namely familial transmission and affiliative transmission. Familial transmission occurs when the character Ruqayyah tells her traumatic memory directly to her second child, Hassan. As for the affiliative transmission experienced by the figures of Nyonya Bayan and Abid through photography, recordings, and document testimonies from eyewitnesses.